Dynamic Information Transparency and Timeliness of Financial Reporting: Opportunistic Theory - Lubis, Rizki Mulia; Siregar, Fatahuddin Aziz; Hasibuan, Abdul Nasser; Nasirin, Wanda Khairun; Daulay, Nurfia Sintia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The delay in financial reporting among Sharia-listed manufacturing companies poses a challenge in leveraging dynamic information transparency to influence timely financial reporting, aligning with Opportunistic Theory. This study aims to analyze financial aspects and corporate governance's impact on reporting timeliness, with tax avoidance as a mediator. Employing Purposive Sampling with 111 manufacturing firms, the SEM-PLS formative model reveals ROA, ROE, DAR, DER, independent board, and audit committee individually affect reporting timeliness. Additionally, tax avoidance significantly mediates the relationship between financial ratios, governance, and reporting punctuality. This suggests the crucial role of tax management in steering corporate decisions and highlights implications for sustainable tax policies, minimizing adverse impacts on financial reporting integrity.